Food web consequences of an evolutionary arms race: Molluscs subject to crab predation on intertidal mudflats in Oman are unavailable to shorebirds. (13th November 2017) - Bom, Roeland A.; de Fouw, Jimmy; Klaassen, Raymond H. G.; Piersma, Theunis; Lavaleye, Marc S. S.; Ens, Bruno J.; Oudman, Thomas; van Gils, Jan A.
Abstract: Aim: Molluscivorous shorebirds supposedly developed their present wintering distribution after the last ice age. Currently, molluscivorous shorebirds are abundant on almost all shores of the world, except for those in the Indo‐West Pacific (IWP). Long before shorebirds arrived on the scene, molluscan prey in the IWP evolved strong anti‐predation traits in a prolonged evolutionary arms race with durophagous predators including brachyuran crabs. Here, we investigate whether the absence of molluscivorous shorebirds from a site in Oman can be explained by the molluscan community being too well‐defended. Location: The intertidal mudflats of Barr Al Hikman, Oman. Methods: Based on samples from 282 locations across the intertidal area the standing stock of the macrozoobenthic community was investigated. By measuring anti‐predation traits (burrowing depth, size and strength of armour), the fraction of molluscs available to molluscivorous shorebirds was calculated. Results: Molluscs dominated the macrozoobenthic community at Barr Al Hikman. However, less than 17% of the total molluscan biomass was available to shorebirds. Most molluscs were unavailable either because of their hard‐to‐crush shells, or because they lived too deeply in the sediment. Repair scars and direct observations confirmed crab predation on molluscs. Although standing stock densities of the Barr Al Hikman molluscs were of the same order of magnitude as at intertidal mudflat areas where molluscivorous shorebirds are abundant, the molluscan biomass available to shorebirds was distinctly lower at Barr Al Hikman. Main conclusions: The established strong molluscan anti‐predation traits against crabs precludes molluscan exploitation by shorebirds at Barr Al Hikman. This study exemplifies that dispersal of "novel" predators is hampered in areas where native predators and prey exhibit strongly developed attack and defence mechanisms, and highlights that evolutionary arms races can have consequences for the global distribution of species.